Relevance And Analysis Of The Rights And Obligations Of Husband Wife In The Book Irsyadul Ibad Ila Sabilirrosyad - Khozinatul Asrori (Universitas Muhammadiyah Bandung, 2025)
The discussion in this study is about the rights and obligations of husband and wife according to Zainuddin bin Abdul Aziz Al-Malibary in his work the book Irsyadul Ibad Ila Sabilirrosyad which is based on certain hadiths. This study is important to see the dynamics of understanding of leading ulama figures who have a broad and strong influence in world society, as well as ulama who produce many works which are often used as references in normative-theological studies in certain circles. This research is library research with a descriptive approach using primary book sources Irsyadul Ibad Ila Sabilirrosyad by Zainuddin bin Abdul Aziz Al-Malibary. The result is that Zainuddin bin Abdul Aziz Al-Malibary's thoughts about the rights and obligations of husband and wife cannot be separated from the social conditions of society at that time. In the context of the modern world, Zainuddin bin Abdul Aziz Al-Malibary's thoughts have had quite a big influence, however, not all of his thoughts are still relevant today. Thus, it is very likely that there will be a need for new interpretations of several similar works which are still used as references in various problems that arise.